Analisis Distribusi Curah Hujan Menggunakan ABM, Mononobe, Van Breen terhadap Distribusi Curah Hujan Aktual pada Stasiun Klimatologi Jambi - Muhammad Indra Kelana; Amsori M Das; Dwitya Okky Azanna; Emelda Raudhati (Jurnal Talenta Sipil, 2026)
The rainfall distribution pattern serves to obtain a rainfall distribution pattern for a region that can be used as a consideration in calculating and analyzing rainfall data, especially hourly rainfall data, as a basis for determining flood planning. This research aims to analyze the distribution and pattern of rainfall at the Jambi Climatology Station; and to analyze the suitability of the empirical method's distribution and rainfall pattern against the actual rainfall observed in the field. The research method used is the Alternating Block Method (ABM), Mononobe, and Van Breen. Based on the suitability test of the empirical rainfall distribution and pattern against the actual rainfall distribution, it is found that the rainfall distribution that most closely resembles field conditions is the ABM method, with a fit of 6 out of 11 rainfall events. The bell-shaped rainfall pattern and the combination of bell-shaped and inverted bell patterns have a fit of 4 out of 11 rainfall events.